2023
DOI: 10.3390/ani13030445
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals and Percentiles for Hematologic and Serum Biochemical Values in Captive Bred Rhesus (Macaca mulatta) and Cynomolgus Macaques (Macaca fascicularis)

Abstract: Several physiological characteristics and housing conditions are known to affect hematologic and serum biochemical values in macaques. However, the studies that have been conducted either report values calculated based on a small number of animals, were designed specifically to document the effect of a particular condition on the normal range of hematologic and serum biochemical values, or used parametric assumptions to calculate hematologic and serum biochemical reference intervals. We conducted a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…In marmosets, higher levels of Fe in adult males compared to juvenile males have been previously described [ 6 ]. In rhesus and cynomolgus macaques, a similar effect has also been observed [ 15 ]. Other research groups have also reported higher levels of cholesterol, creatinine, red blood cells, HGB, HCT [ 2 , 7 ] in males compared to females and higher levels of MCV, MCH [ 7 ], and PLT [ 5 ], which we did not conclude in this article.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…In marmosets, higher levels of Fe in adult males compared to juvenile males have been previously described [ 6 ]. In rhesus and cynomolgus macaques, a similar effect has also been observed [ 15 ]. Other research groups have also reported higher levels of cholesterol, creatinine, red blood cells, HGB, HCT [ 2 , 7 ] in males compared to females and higher levels of MCV, MCH [ 7 ], and PLT [ 5 ], which we did not conclude in this article.…”
Section: Discussionsupporting
confidence: 60%
“…However, in order to present the reader with a usable set of reference intervals, the decision was made to focus only on parameters that were judged clinically relevant. Delta values > 5% [ 15 ] and with a p -value ≤ 0.001 were regarded to be clinically relevant. Figures show all delta values calculated for the comparisons for each variable with the differences > 5% in bold.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations